Optimization of quenching process in hot stamping of boron alloyed steel - Mohd Nazeri, Mohd Annuar (2013)
This thesis explained the effect of quenching process parameters in hot press forming that has been used in automotive industry to manufacture metallic parts with high specific strengths. Optimum cooling system need to be considered during the quenching process in hot stamping to achieve the highest strength. The material that had been used in this hot press forming process was boron alloyed steel (22MnB5) that will produce the highest martensite content after being hot stamped. After being heated in the furnace up to 950 0C until 10 minutes, the specimens were pressed at 40 bar by using the hydraulic power press and quenched. The investigations were studied on the microstructure and its hardness properties. Every specimen was prepared for the mechanical testing. To get the optimum parameters, ANOVA were used by using the full factorial design. The responses were studied on hardness value. The result shows that by increasing the quenching time and flow rate will increase the hardness value of the specimen while lowering the coolant temperature will increase the hardness value. The heat transfers by conduction were optimum during the pressure holding time process so the optimum cooling systems hardly effect the formation of the blank. The value of hardness are directly proportional with the formation of martensitic microstructure but it was impossible to achieve a fully martensite structure after the blank being hot stamped. The formation of martensite was due to the heating of the blank until its austenite phase and rapid cooling that make the carbon atom stretch along one direction. Besides martensite structure, the formation of bainite and retained austenite structure also appeared after the blank being hot stamped. to achieve an optimum hardness value up to 551.3 HV0.5, the specimen should be quenched at 7 second with the flow rate of 40 L/min and coolant temperature of 27 0C.